Circulating FGF-23 Is Associated With Increased Risk of Osteoporosis and Fractures in Hemodialysis Patients: A Prospective Observational Study - Dong Liu; Hongyan Yang; Qirong Liao; Baocao Chang; Weiwei Zhang; Xiaoxiong Li; Jinping Li; Mingliang Hou; Linqiu Ma; Yating Liu; Jing Lu; Rui Zhou (International Journal of Clinical Practice)
Conclusion: High concentrations of circulating FGF-23 were associated with the risk of osteoporosis and fractures, including vertebral fractures and hip fractures. FGF-23, along with bALP, CTX, and OC, may be used as a serum biomarker for predicting the risk of osteoporosis and fractures in patients with hemodialysis.